2012
DOI: 10.3389/fnins.2012.00032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Frame-Constrained Fix-Pixel-Value and Frame-Free Spiking-Dynamic-Pixel ConvNets for Visual Processing

Abstract: Most scene segmentation and categorization architectures for the extraction of features in images and patches make exhaustive use of 2D convolution operations for template matching, template search, and denoising. Convolutional Neural Networks (ConvNets) are one example of such architectures that can implement general-purpose bio-inspired vision systems. In standard digital computers 2D convolutions are usually expensive in terms of resource consumption and impose severe limitations for efficient real-time app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…Furthermore, as we have shown, spiking DBNs can process data with very low latency, without having to wait for a full frame of data, which can be further improved if individual units of the DBN compute in parallel, rather than updating each unit in sequence. This advantage has been recognized for many years for feed-forward convolutional networks, in which almost all operations can be efficiently parallelized, and has led to the development of custom digital hardware solutions and spike-based convolution chips (Camuñas Mesa et al, 2010; Farabet et al, 2012), which through the use of the Address Event Representation (AER) protocol, can also directly process events coming from event-based dynamic vision sensors (Lichtsteiner et al, 2008). For such architectures (Pérez-Carrasco et al, 2013) have recently developed a similar mapping methodology between frame-based and event-driven networks that translates the weights and other parameters of a fully trained frame-based feed-forward network into the event-based domain, and then optimizes them with simulated annealing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as we have shown, spiking DBNs can process data with very low latency, without having to wait for a full frame of data, which can be further improved if individual units of the DBN compute in parallel, rather than updating each unit in sequence. This advantage has been recognized for many years for feed-forward convolutional networks, in which almost all operations can be efficiently parallelized, and has led to the development of custom digital hardware solutions and spike-based convolution chips (Camuñas Mesa et al, 2010; Farabet et al, 2012), which through the use of the Address Event Representation (AER) protocol, can also directly process events coming from event-based dynamic vision sensors (Lichtsteiner et al, 2008). For such architectures (Pérez-Carrasco et al, 2013) have recently developed a similar mapping methodology between frame-based and event-driven networks that translates the weights and other parameters of a fully trained frame-based feed-forward network into the event-based domain, and then optimizes them with simulated annealing.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, this offers increased flexibility to change neuronal parameters after training, whereas our method uses the accurate Siegert-approximation of spike rates already during the training of a bi-directional network, and does not require an additional optimization phase. The advantages of spike-based versus digital frame-based visual processing in terms of processing speed and scalability have been compared in Farabet et al (2012), where it was also suggested that spike-based systems are more suitable for systems that employ both feed-forward and feed-back processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of spiking deep networks together with event-based sensors has been considered in previous studies, for a example, through a spiking CNN receiving DVS spikes [5], [6]. Spiking deep networks have also been implemented in hardware, for example, a spiking DBN was implemented on a hardware platform and interfaced to a DVS [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…In one case, the convolutional neural network (CNN) units were translated into biologically inspired spiking units with leaks and refractory periods. [4,5] SNNs can output results even after the first spike is produced, [6] whereas in ANNs the result is only available when all the layers have been totally processed. [6] This scheme is based on the principle of rescaling the weights to avoid approximation errors in SNNs due to either excessive or too little firing of the neurons.…”
mentioning
confidence: 99%